Associations Between Urological Chronic Pelvic Pain Syndrome Symptom Flares, Illness Impact, and Health Care Seeking Activity: Findings From the Multidisciplinary Approach to the Study of Chronic Pelvic Pain Symptom Patterns Study. Issue 4 (11th April 2023) - Sutcliffe, Siobhan; Newcomb, Craig; Bradley, Catherine S.; Clemens, J. Quentin; Erickson, Bradley; Gupta, Priyanka; Lai, H. Henry; Naliboff, Bruce; Strachan, Eric; Stephens-Shields, Alisa
Abstract : Purpose: Most studies on interstitial cystitis/bladder pain syndrome and chronic prostatitis/chronic pelvic pain syndrome use typical or average levels of pelvic pain or urological symptom intensity as their outcome, as both are associated with reduced quality of life. Symptom exacerbations or "flares" have also been found to be associated with reduced quality of life, but no studies, to our knowledge, have investigated whether these associations are independent of typical pelvic pain levels and thus might be useful additional outcome measures (or stated differently, whether reducing flare frequency even without reducing mean pain intensity may be important to patients). Materials and Methods: We used screening visit and weekly run-in period data from the Multidisciplinary Approach to the Study of Chronic Pelvic Pain Symptom Patterns Study to investigate associations between flare frequency and multiple measures of illness impact and health care seeking activity, independent of typical nonflare and overall pelvic pain levels. Results: Among the 613 eligible participants, greater flare frequency was associated with worse condition-specific illness impact (standardized β coefficients=0.11-0.68, P trends < .0001) and health care seeking activity (odds ratios=1.52-3.94, P trends .0039 to < .0001) in analyses adjusted for typical nonflare and overall pelvic pain levels. Experiencing ≥1/d was also independently associated with worse general illness impact (standardized β coefficients=0.11-0.25). Conclusions: Our findings suggest that flare frequency and possibly other flare characteristics may be worth considering as additional outcome measures in urological chronic pelvic pain syndrome research to support the development of new preventive and therapeutic flare strategies.